Defect controlled transverse compressive strength of polyethylene fiber laminates. (1st January 2015) - O'Masta, M.R.; Deshpande, V.S.; Wadley, H.N.G.
Highlights: Transverse compressive strength of cross-ply UHWMPE composites is shown to exceed that of high strength steels. Missing fiber and tunnel crack defects are discovered in composite laminates. Missing fiber defects degrade the transverse compressive strength. A load shielding model predicts the strength versus defect distribution relation. Abstract: Using a combination of optical and ultrasonic imaging in conjunction with micro-X-ray tomography, we have identified the existence of two classes of defects in [0°/90°] cross-ply polymeric composites made from ultrahigh molecular weight polyethylene (UHMWPE) fibers and thermoplastic resins, and investigated their effects upon the transverse compressive strength of laminates of various thicknesses and lateral dimension. One defect type consisted of equal spaced tunnel cracks that resulted from anisotropic thermal contraction of the laminates after processing. The second consisted of void-like defects resulting from missing groups of fibers. Like the tunnel cracks, this defect extended many centimeters in a ply's fiber direction. While tunnel cracks were healed upon out of plane compression, and therefore have little effect on a laminates out of plane compressive strength, the missing fiber defects significantly degraded the compressive strength. However, the degradation was reduced by increasing the laminate thickness. Compression tests using pressure sensitive film and acoustic emission monitoring reveal that regions containing missing fiber defects are shielded from load by defect free regions, which then fail at lower sample pressure during loading. A simple statistical model is used to simulate the distribution of missing fiber defects as local reductions in ply thickness, and reproduced the contrast observed in optical and ultrasonic images, as well as the reduction in out of plane compressive strength observed in experiments.